Exploring the Role of IND–COL as a Moderator in the Comprehensive Service Evaluation Model - Sharma, Piyush; Chen, I.S.; Luk, S.T. (Routledge, 2012)
Prior research shows that a comprehensive service evaluation model best explains the relationships among perceived service quality, sacrifice, value, satisfaction, and behavioral intentions; however, it ignores the influence of culture on these relationships. This article tests the moderating effects of the individualism–collectivism dimension of national culture on all the relationships in the comprehensive service evaluation model. Findings from a large-scale study across six retail categories (cosmetics, electronics, fashion, jewelry, telecom services, and department stores) show significant differences in the strength of relationships in the service evaluation process between shoppers from individualistic versus collectivistic cultures.